Revolutionizing the treatment for nasopharyngeal cancer: the impact, challenges and strategies of stem cell and genetically engineered cell therapies - Looi, Chin-King; Loo, Ee-Mun; Lim, Heng-Chee; Chew, Yik-Ling; Chin, Kok-Yong; Cheah, Shiau-Chuen; Goh, Bey Hing; Mai, Chun-Wai (Frontiers in Immunology, 2024)
Nasopharyngeal carcinoma (NPC) is a distinct malignancy of the nasopharynx and is consistently associated with the Epstein-Barr virus (EBV) infection. Its unique anatomical location and complex aetiology often result in advanced-stage disease at first diagnosis. While radiotherapy (RT) and chemotherapy have been the mainstays of treatment, they often fail to prevent tumour recurrence and metastasis, leading to high rates of treatment failure and mortality. Recent advancement in cell-based therapies, such as chimeric antigen receptor (CAR)-T cell therapy, have shown great promise in hematological malignancies and are now being investigated for NPC. However, challenges such as targeting specific tumour antigens, limited T cell persistence and proliferation, and managing treatment-related toxicities must be addressed. Extensive research is needed to enhance the effectiveness and safety of these therapies, paving the way for their integration into standard clinical practice for better management of NPC and a better quality of life for human health.